A Study on Knowledge, Awareness, and Medication Adherence in Patients with Hypertension from a Tertiary Care Centre from Northern Sri Lanka - S. Pirasath; T. Kumanan; M. Guruparan (International Journal of Hypertension)
Objective. To assess the patient’s knowledge and awareness about hypertension and adherence to antihypertensive medication among hypertensive patients with validated Morisky questionnaires in a tertiary care centre of northern Sri Lanka. Methods. A cross-sectional descriptive comparative study was carried out at Teaching Hospital Jaffna, from January 2017 to April 2017. Hypertensive patients were recruited by systematic randomized controlled sampling and interviewed with validated Morisky questionnaires to assess their knowledge about hypertension. Data were analyzed using SPSS (version 21) analytical package. Results. 73 of 303 patients were males. 69.9% of patients had adequate knowledge about hypertension. 40.5% of patients were unaware of their disease status. 75.8% of patients could not recall their blood pressure values at the time of diagnosis. 72.3% of patients were unaware of their values of blood pressure during their last outpatient clinic visit. 48.2% of patients had awareness of target organ damage due to hypertension (kidney, 72, 23.7%; heart, 128, 42.2%; brain, 140, 46.7%; eye, 42, 13.8%). Most of the patients had poor drug compliance. The most common reasons for nonadherence were forgetfulness (70, 23.1%) and interruptions of daily routine (53, 17.5%). Conclusion. The knowledge about hypertension among majority of patients was reasonable. But they were unaware of their disease status. The drug compliance among them was poor. Forgetfulness and interruptions of daily routine were common reasons attributed for nonadherence.